Oceans of churn: Australia's 2020 defence strategic update and the Indo-Pacific. (2nd January 2021) - Bhattacharya, Deekhit; Eadon, Ashley
ABSTRACT: Australia published a Strategic Update in 2020 to its 2016 Defence White Paper. The update represents a portentous shift in Australia's understanding and response to its strategic environment. China's increasingly belligerent stance, its use of grey-zone activities and an increasingly jittery United States have pushed Australia to actively seek robust anti-access/area denial (A2AD) capabilities. In addition, Australia intends to focus on its neighbourhood while shedding its anxieties regarding the Quad. The piece aims to briefly contextualise the ramifications of the update with its motivations. It also analyses Chinese behaviour on the world stage and argues for greater synergy in defence coordination between the Quad partners.